KISAH ORANG TURKI DALAM SEJARAH ISLAM DI JAMBI - Ali Muzakir (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2013)
Little has been written on the history of Jambi. The early history of thesultanate of Jambi roughly coincided with the advent of Islam, through precise dates are impossible. According to legends and Jambian folklore that the forefather of the sultan’s family had been a foreigner, originally from Turkey. In the nineteenth century, Turkey was seen as the embodiment of the Jambian ideal of near-divine strength and succor; and as savior in the times of emergency. Hope of military aid from Turkey had soared, despite the fact that just a rumor and rhetoric.Keywords: History, History of Jambi, Jambi Islam